Current follower based reconfigurable integrator/differentiator circuits with passive and active components׳ reuse. Issue 2 (February 2015) - Alzaher, Hussain
Abstract Reconfigurable integrator/differentiator circuits based on the current follower are presented. They are essential for realizing configurable analog blocks (CABs) for field programmable analog arrays (FPAAs). The proposed circuits provide functional reconfigurations and components reuse. These functions provide flexibility in the area of filter design within CAB architectures. Circuits based on current follower have the potential to operate at higher frequency ranges and offer improved linearity over their counterparts based on the operational amplifier and transconductance amplifier, respectively. No switches are used in a signal path in order to avoid degrading the frequency response of the proposed circuits. A CMOS current follower realization compatible with implementation of the proposed designs is adopted. Experimental results obtained from a standard 0.35 µm CMOS process are provided.